Nephrogenic diabetes insipidus associated with temozolomide therapy in a patient with grade IV astrocytoma - Zayd Fargouche; Martin Manderlier; Anne-Pascale Meert; Louis Wolff; Maxime Ilzkovitz (European Journal of Case Reports in Internal Medicine)
Temozolomide (TMZ), an alkylating agent used in glioblastoma multiforme and anaplastic astrocytoma treatment, is generally associated with side effects like myelosuppression and nausea. This case report describes a rare occurrence of nephrogenic diabetes insipidus (NDI) in a 45-year-old male with grade IV astrocytoma undergoing TMZ therapy. Following TMZ discontinuation due to haematological toxicity, the patient developed significant polyuria and hypernatremia. Central diabetes insipidus was initially suspected, but limited improvement with desmopressin and normal endocrine investigations suggested renal involvement. The diagnosis of partial NDI was made and linked to TMZ-induced acute tubulointerstitial nephropathy (ATN). Despite symptom onset coinciding with TMZ administration, recovery was delayed after discontinuation, implicating possible lasting tubular damage. Although the precise pathogenesis remains uncertain, it may involve TMZ-induced renal tubule inflammation, affecting aquaporin-2 expression and water retention. In this case, management of NDI included adequate intravenous hydration, oral fluid restriction, and progressive resolution of polyuria without the need for diuretic or non-steroidal anti-inflammatory drug. This case emphasizes the need for vigilance regarding renal complications, particularly NDI, in patients receiving TMZ, warranting careful monitoring of electrolytes, renal function and diuresis to ensure prompt identification and management of this rare but serious side effect.